The possible involvement of SIK2 in diabetic retinopathy - Ersoy, Burcu. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2015., 2015)
Diabetic Retinopathy (DR) is one of the most common complications of diabetes and in advanced stages it is characterized by vascular abnormalities and neuronal degeneration. It is widely accepted that the functional changes in retinal Müller glia, collectively named as gliosis, constitutes an important factor leading to the dysfunction and degeneration of neurons in the development of DR. Our earlier research indicated that chronic hyperglycemia results in decrease in insulin-dependent survival of cultured Müller cells with concomitant increase in SIK2 activity and expression. Further studies suggest that SIK2 may act as a negative regulator of insulin-induced survival pathway and contributes to hyperglycemia-induced death of Müller glia through downregulation of IRS1 activation in vitro. These findings raise the possibility that hyperglycemia induced upregulation of SIK2 expression and/or activity may contribute to development of DR. In this study, to provide evidence towards potential involvement of SIK2 in DR, we investigated modulation of its expression and activity under hyperglycemic conditions using Streptozotocin-induced DR model rats. Analysis of 2-week, 4-week, 8-week diabetic and the age-matched control retinae showed that gliosis of Müller cells gradually increased and spanned the entire thickness of the retina by time, beginning from the 2nd week of diabetes. On the other hand, cell death in retina was first observed in ganglion cells within 4 weeks of diabetes onset then became apparent in Müller cells and neurons of inner nuclear layer in the 8th week of diabetes. Although SIK2 level and expression pattern in the retina showed no change in response to diabetes, its activity seemed to be transiently increased in 2-week and 4-week diabetic retina. No change in SIK2 activity was observed in 8-week diabetic retina compared to control retina. Moreover, co-Immunoprecipitation results demonstrated that SIK2 and IRS1 interaction was upregulated beginning from the 4th week of diabetes supporting the possibility that IRS1 can be negatively regulated by SIK2 leading to the impairment of insulin-induced cell survival in diabetic retina.
Keywords: Diabetic retinopathy -- Popular works.